2019
DOI: 10.1101/521740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational modeling reveals frequency modulation of calcium-cAMP/PKA pathway in dendritic spines

Abstract: Dendritic spines are the primary excitatory postsynaptic sites which act as subcompartments of signaling. Ca 2+ is often the first and rapid signal. Downstream of calcium, the cAMP/PKA pathway plays a critical role in the regulation of spine formation, morphological modifications, and ultimately, learning and memory. While the dynamics of calcium are reasonably well-studied, calcium-induced cAMP/PKA dynamics are not fully explored. In this study, we present a well-mixed model for the dynamics of calcium-induce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 134 publications
(108 reference statements)
0
30
0
Order By: Relevance
“…Our results show that spatial localization of enzymes on the spine membrane and in the cytoplasm can alter the temporal response of cAMP to induced calcium transients. Thus, in addition to kinetic properties as shown previously (15), we predict that the spatial organization of molecules in the dendritic spine can affect how cAMP/PKA dynamics respond to calcium input.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Our results show that spatial localization of enzymes on the spine membrane and in the cytoplasm can alter the temporal response of cAMP to induced calcium transients. Thus, in addition to kinetic properties as shown previously (15), we predict that the spatial organization of molecules in the dendritic spine can affect how cAMP/PKA dynamics respond to calcium input.…”
Section: Introductionmentioning
confidence: 53%
“…It is also well known that calcium spikes are necessary for changes in cAMP concentrations, but only certain bursts of calcium spikes increase cAMP levels in neurons (11). The dynamics of calcium-induced cAMP has been modeled by us and others (15,27,48,74) with a focus on identifying the mechanisms underlying interdependent oscillations. We showed that cAMP is primarily sensitive to the longer timescale effects of calcium rather than the shorter timescales (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fluorescence experiments have shown that the dendritic spine necks act as a diffusion barrier to calcium ions, preventing ions from entering the dendritic shaft [59]. Complementary to this and other experiments, various physical models solving reaction-diffusion equations in idealized geometries have been developed to further interrogate the structure-function relationships [41,53,[64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%